Platelet Receptor Shedding - Gardiner, E.; Al-Tamimi, M.; Robert, A.; Berndt, Michael (Springer, 2012)
Receptor shedding is a mechanism for irreversible removal of transmembrane cell surf.1ce receptors by proteolysis of the receptor at a position near the extracellular surface of the plasma membrane. This process generates a soluble ectodomain fragment and a membrane-associated remnant fragment, and is distinct from loss of receptor surface expression by internalization or microparticle release or secretion of alternatively spliced soluble forms of receptors lacking a transmembrane domain. There has been an increased focus on new methods for analyzing shedding of platelet glycoprotein (GP)Ib-IX-V and GPVI because these receptors are platelet specific and are critical for the initiation of platelet adhesion and activation in thrombus formation at arterial shear rates. Platelet receptor shedding provides a mechanism for downregulating surface expression resulting in loss of ligand binding, decreasing the surface density affecting receptor cross linking and signalling and generation of proteolytic fragments that may be functional and/ or provide platelet-specific biomarkers.